(3efgGL GdOcGf hOSJhQ GdCYjGf aj JQcjH GdCOhjI GdfGaYI ddCHOGfs - (3Gdchgjf GdYWGQ GdGSQGFjdj , OGhO Hf CHj fUQ Hf MaGX, CHh Gdefj,J (B608 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3eHJhQ GdChd hRf fUa OQge efg eY ZjQg s
(3BNQgG (B:s
(3heG bO LQHJg eeG bGe YfOi hde jJZjQ bO PcQJ hgPG GdbOQ cGa dc EPG JCedJg , aCfYe GdfXQ ajg s
(3hJTJed Ydi GhQGb HNW MOjK eZGjQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B143s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B188 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1870s
Keywords: (3GdWHs